PENATAAN KAMPUNG NELAYAN DENGAN PENDEKATAN ARSITEKTUR EKOLOGI DI KELURAHAN BAGAN DELI KOTA MEDAN - Fachrudin, Hilma Tamiami; Rahmadani, Fadila (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: Indonesia is a maritime country that has abundant marine natural resources, with optimal and wise utilization, it will be a promising source of income for both the local community as well as the local area. Therefore, the infrastructure and maritime-related arrangements along the coast and the port are things that must be considered and developed. Gabion Port is one of the ports with the largest marine products in the province of North Sumatra, especially in the city of Medan. This port is located near Bagan Deli village which has not yet been optimally arranged and it has economic problems and serious environmental hygiene problems, so that with the application of the concept of ecological architecture can answer the existing problems through its principles. Some applications of ecological concepts in this arrangement can be seen from material aspects, energy aspects, building orientation, and utility aspects. The method used is the glass box method, by looking at elements that need to be applied to support the socio-economic activities of the local community. The results of this paper are in the form of the concept of structuring fishing villages which can be a solution to slum environmental problems and helps improve the economic level of local communities.Keyword: fishing village, ecological architecture, bagan deliÂ Abstrak: Indonesia merupakan negara maritim yang memiliki sumber daya alam kelautan yang berlimpah, dengan pemanfaatan secara optimal dan bijak akan menjadi sumber pendapatan yang menjanjikan baik bagi masyarakat sekitar maupun daerah setempat. Untuk itu infrastruktur dan penataan terkait kelautan sepanjang pantai dan pelabuhan merupakan hal yang harus diperhatikan dan dikembangkan. Pelabuhan Gabion merupakan salah satu pelabuhan dengan hasil laut terbesar di kawasan provinsi Sumatera Utara khususnya kota Medan. Pelabuhan ini berada di dekat kelurahan bagan deli yangmana belum tertata secara optimal, serta memiliki masalah perkeonomian dan juga memiliki permasalahan kebersihan lingkungan yang cukup serius, sehingga dengan penerapan konsep arsitektur ekologi dapat menjawab permasalahan yang ada melalui prinsip-prinsipnya. Beberapa penerapan konsep ekologi pada penataan ini dapat dilihat dari aspek material, aspek energy, orientasi bangunan, dan aspek utilitas. Metode yang digunakan adalah metode glass box,dengan melihat elemen elemen yang perlu diterapkan untuk mendukung aktivitas social ekonomi masyarakat setempat. Hasil penelitian ini berupa konsep penataan kampung nelayan yang dapat menjadi pemecahan masalah lingkungan kumuh serta membantu meningkatkan taraf perekonomian masyarakat setempat.Kata Kunci: Kampung Nelayan, Arsitektur Ekologi, Bagan Deli